Law Enforcement on Consumer Protection for Online Counterfeit Goods Purchases - Nabila, Sofia; Hasmiati, Rahmatullah Ayu; Pratama, Rio Arif (Bacarita Law Journal, 2025)
The rapid advancement of information technology has brought significant changes to the world of commerce, particularly through e-commerce. Online buying and selling systems offer convenience to consumers, but they also present new challenges, one of which is the increasing circulation of counterfeit goods. In Indonesia, consumer protection regulations are outlined in Law Number 8 of 1999 on Consumer Protection and Law Number 11 of 2008 on Electronic Information and Transactions. However, despite the clear regulations, the implementation of consumer protection in online transactions still faces obstacles, especially in regions such as Samarinda. This study aims to analyze consumer protection laws in Samarinda, focusing on the roles of Non-Governmental Consumer Protection Agency Borneo and the Police. The findings indicate that protection efforts include consumer education regarding their rights and complaint channels to address counterfeit goods cases. However, low consumer awareness remains a major challenge to the effectiveness of these protections. Moving forward, there is a need to enhance education about the risks of online transactions and improve coordination between agencies to minimize online fraud. Consumer protection depends not only on regulations but also on the active role of society and relevant institutions in creating a safer e-commerce ecosystem. Collaboration among agencies, along with heightened consumer awareness, is key to tackling the problem of counterfeit goods in the online marketplace.